Analisis Peran Komunikasi Dalam Pengaruhnya Terhadap: Kinerja, Produktivitas, Dan Penjualan - Azka Rizqon Irawan (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In the world of work, communication is at the root of all important aspects inherent in the person of each individual, helping to achieve goals both personally and organizationally. This study was made using literacy study methodology which found that effective communication is associated with increased productivity, better organizational health, and employee satisfaction. Identification of communication styles is also considered to play an important role in building positive interactions with others and play a key role in building personal branding. Good communication can help improve well-being in relationships and play a role in personal and professional growth and success. Case studies also show that clear internal communication positively affects employee performance, while lack of communication can lead to misunderstandings and decrease productivity. In the context of sales, communication in marketing also plays an important role in increasing sales volume by presenting clear and precise information about the product to build consumer trust.